2022
DOI: 10.1038/s41556-022-00961-5
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell analysis of endometriosis reveals a coordinated transcriptional programme driving immunotolerance and angiogenesis across eutopic and ectopic tissues

Abstract: Endometriosis is characterized by growth of endometrial-like tissue outside of the uterus affecting many women in their reproductive age, causing years of pelvic pain and potential infertility. Its pathophysiology remains largely unknown, limiting diagnosis and treatment. We characterized peritoneal and ovarian lesions at single-cell transcriptome resolution and compared to matched eutopic endometrium, control endometrium, and organoids derived from these tissues, generating data on over 100,000 cells across 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
117
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(133 citation statements)
references
References 109 publications
13
117
3
Order By: Relevance
“…Abnormal activation and increased numbers of macrophages along with elevated levels of proinflammatory cytokines such as IL-1β, IL6, IL8, and TNFα are present in the peritoneal fluid of patients with endometriosis 11 , 43 , 44 . Moreover, analysis of macrophages within the pelvic cavity and endometriotic lesions of patients has demonstrated enhanced biological activities related to angiogenesis, neurogenesis, antigen processing and presentation, and tissue adhesion 45 , 46 . Our previous studies in mice have demonstrated that niclosamide treatment reduced inflammation in the peritoneal fluid, lesions, pelvic organs (uterus and vagina), and dorsal root ganglion 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal activation and increased numbers of macrophages along with elevated levels of proinflammatory cytokines such as IL-1β, IL6, IL8, and TNFα are present in the peritoneal fluid of patients with endometriosis 11 , 43 , 44 . Moreover, analysis of macrophages within the pelvic cavity and endometriotic lesions of patients has demonstrated enhanced biological activities related to angiogenesis, neurogenesis, antigen processing and presentation, and tissue adhesion 45 , 46 . Our previous studies in mice have demonstrated that niclosamide treatment reduced inflammation in the peritoneal fluid, lesions, pelvic organs (uterus and vagina), and dorsal root ganglion 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of macrophages in the human endometriotic microenvironment shares some similar characteristics with those found within the murine peritoneal cavity in this study. In the pelvic cavity and eutopic and ectopic endometrium of endometriosis patients, both CCR2 + monocyte-derived and tissueresident macrophages were distinguished using scRNA-seq and traditional methods such as flow cytometry 45,46,[58][59][60] . FOLR2 + macrophages were also identified in the endometriotic lesions in patients 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that immune dysfunction may play an important role in the pathology of endometriosis. Moreover, Tan Y et al analyzed the transcriptome of endometrium and endometriotic lesions using single-cell RNA sequencing and provided a landscape of the endometriosis microenvironment [ 14 ]. In general, evaluating transcriptome datasets facilitates the assessment of overall gene functions and structures to investigate the molecular signatures predictive of certain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although bulk tissuebased transcriptomics studies [12][13][14] have revealed basic information, convincing evidence regarding the molecular mechanisms involved in AS-related endometrial dysfunction remains elusive. Advancements in single-cell RNA sequencing (scRNA-seq) of the human endometrium 15 and endometrial organoid culture systems 16 have enabled a deeper understanding of cellular cartography and cell-to-cell communication (CCC) in endometrial pathologies such as endometriosis 17 and atrophic endometrium 18 .…”
Section: Introductionmentioning
confidence: 99%